LAG-3+ tumor-infiltrating lymphocytes ameliorates overall survival in triple-negative breast cancer patients - Hu, Guoming; Wang, Shimin; Wang, Songxiang; Ding, Qiannan; Huang, Liming (Frontiers in Oncology, 2023)
Purpose: Immune checkpoint molecule Lymphocyte-activating gene-3 (LAG-3), which is expressed on active lymphocytes, has proven to be associated with immunosuppression and cancer progression in a variety of solid tumors. However, the role of LAG-3+lymphocytes in human breast cancer (BC) is still not conclusive. We therefore performed a meta-analysis to clarify the role of these cells in prognosis prediction for BC. Methods: We searched PubMed, Embase and EBSCO to identify the studies evaluating the association of LAG-3+lymphocyte infiltration and overall survival (OS) and/or disease-free survival (DFS) in BC patients, then combined extracted data with STATA 12.0. Results: Eight published studies involving 5859 BC patients were incorporated into this meta-analysis. We noted that high number of LAG-3+tumor-infiltrating lymphocytes was not appreciably associated with OS and DFS in BC patients. Strikingly, in stratified analyses based on molecular type of BC, LAG-3+lymphocyte infiltration was remarkably associated with better OS rather than DFS in triple-negative breast cancer (TNBC); while it significantly influenced neither OS nor DFS in Her2 positive BC; However, increased density of these lymphocytes indicated a trend for better OS in Her2-positive BC. Besides, we found that LAG-3+lymphocyte infiltration was also remarkably associated with prolonged OS in Her2-positive BC patients when they were measured by immunohistochemistry (IHC). In addition, elevated number of these lymphocytes did not correlate with pathological complete response rate or clinicopathological features including lymph node metastasis etc. Conclusion: the infiltration of LAG-3+lymphocytes ameliorates OS in TNBC and Her2-positive BC, implicating that it is a valuable prognostic biomarker, and applications of anti-LAG-3 antagonists may possibly be not a promising therapeutic strategy for human BC especially for TNBC.